COMPLICATIONS OF LOCALLY ADVANCED CERVICAL CANCER AFTER COMPLEX TREATMENT - Khakimov Galib Abdullaevich; Tashmetov Murod Nasirullayevich (Scholar Express Journals, 2025)
Locally advanced cervical cancer (LACC) remains a significant clinical problem worldwide, especially in low- and middle-income countries. Standard complex treatment involves chemoradiation therapy with or without surgical intervention. Despite advances in multimodal management, patients often experience early and late complications that affect quality of life and long-term survival. This article analyzes the types, frequency, and risk factors of complications following complex treatment of LACC, with particular attention to urogenital, gastrointestinal, hematologic, and psychosocial consequences. Evidence from clinical studies and recent literature is discussed, and recommendations for reducing treatment-related morbidity are presented.
Keywords: Cervical cancer; locally advanced; complications